Estimating the proportions of allele frequencies for SERPINA12 pathogenic variants in Japanese patients with Nagashima-type palmoplantar keratosis/keratoderma - Ebata, Aoi; Takeichi, Takuya; Nishida, Kazuki; Chrétien, Basile; Miyazaki, Akira; Yoshikawa, Takenori; Suzuki, Yuika; Tanahashi, Kana; Fukaura, Ryo; Seishima, Mariko; Suga, Yasushi; Muro, Yoshinao; et al. (British Journal of Dermatology, 2025)
Nagashima-type palmoplantar keratoderma (NPPK) is the most common form of palmoplantar keratoderma in Asian populations and is primarily caused by biallelic variants in SERPINB7. As SERPINA12 variants were reported in Chinese patients with NPPK, we analysed SERPINA12 variants in 18 Japanese patients with NPPK lacking biallelic SERPINB7 variants and found significantly higher frequencies of SERPINA12 variants c.635-7A>G and c.656A>G compared with the general population. This suggests a potential digenic effect involving SERPINB7 and SERPINA12, highlighting the need for considering digenic inheritance in NPPK diagnosis and genetic counselling.